Physician Global Assessment as a Disease Activity Measure for Relapsing Polychondritis. Issue 8 (29th April 2022) - Rose, Emily; Ferrada, Marcela A.; Quinn, Kaitlin A.; Goodspeed, Wendy; Arnaud, Laurent; Sharma, Aman; Yoshifuji, Hajime; Kim, Jeff; Allen, Clint; Sirajuddin, Arlene; Chen, Marcus; Grayson, Peter C.
Abstract : Objective: Relapsing polychondritis (RP) is a systemic inflammatory disorder of cartilage that lacks validated disease activity measures. Our objective was to test physician global assessment (PhGA), a measure of disease activity commonly used in rheumatic diseases, in a cohort of patients with RP, which has not been done before. Methods: Adult patients in an observational cohort of RP underwent standardized, comprehensive evaluation at approximately 6‐month intervals. PhGA was scored by 3 physicians from the evaluating institution on a scale of 0–10 for each visit. A random subset of 20 visits was scored by 3 independent physicians not affiliated with the evaluating institution. Treatment change between consecutive visits was categorized as increased, decreased, or unchanged. Results: In total, 78 patients were evaluated over 164 visits. The intraclass correlation coefficient (ICC2, 1 ) for the 3 raters from the evaluating institution was excellent (0.79 [95% confidence interval (95% CI) 0.73, 0.84]) but was poor in the subset of cases scored by the additional raters (ICC2, 1 0.27 [95% CI −0.01, 0.53]). Median PhGA was 3 (range 0–7). PhGA weakly correlated with C‐reactive protein level (rs = 0.30, P < 0.01). In response to increased treatment, median PhGA decreased from 3 (interquartile range [IQR] 2, 4) to 2 (IQR 2, 3) ( P < 0.01) but rarely went to 0. Conclusion: Within a single center, PhGA can be used to quantify disease activity and monitor disease response in RP. Persistent disease activity despite treatment, rather than a relapsing‐remitting pattern, is observed for most patients with RP. Reliability of PhGA may not generalize across different institutions. A validated disease‐specific activity index is needed in RP.